Technological transformation and retail banking competition: Implications and measurement - Jukka Vesala (Bank of Finland, 2000)
The study analyses the effects on banking competition of the changes in banking delivery and information collection technologies and of the rivalry from outside the traditional banking sector.Key implications for monetary, regulatory and competition policies are also addressed. Evidence is provided that liberalization increased banking competition in Europe.In a mostly deregulated environment, technology is argued to be of major importance for competition, The study argues against the prevalent spatial modelling of banking competition due to the difficulty of representing remote access and nonbank activity.Instead, a novel two-stage model (delivery capacity, then loan and deposit pricing decisions) is developed based on multidimensional differentiation theory.According to the results, benefits that clients derive from branch or ATM proximity, additional outlets, or superior service quality can maintain pricing power for banks.Technological development reduces these benefits and generates a permanent increase in competition.The optimal sizes of branch and ATM networks decline.Network cooperation reduces network sizes, but is not necessarily harmful, as price competition is stimulated. An empirical implementation of the model is presented for the Finnish loan and deposit markets.Banks' pricing power is found to be entirely due to their branch network differentiation and size in the loan markets, and to exist mainly in household lending.In contrast, price coordination was found to likely characterize deposit pricing.The ability to distinguish differentiation from collusion is a new contribution.Banks' pricing advantages were found to be diminishing in all lending and especially deposit-taking activities, following the technological development, which indicates reduced significance of branches for clients. Technological development, growing nonbank activity, deepening capital markets and weakening price coordination are found to enhance the efficiency of monetary policy transmission into lending (and deposit) rates.The results are relevant for the common euro area monetary policy, since they show the dependence of the transmission on particular structural and competitive conditions of the banking system.Finally, deregulation of deposit interest rates insulates loan rates from changes in deposit rates and, contrary to what is often argued, does not make loans more costly.
URN:NBN:fi:bof-201408071718
Keywords: 330; banking competition; technological change; delivery networks; monetary policy efficiency; competition policy